Manejo de nitrogênio e tratamento químico sobre a ocorrência de Tilletia Barclayana em arroz irrigado - Zemolin, Carla Rejane (2009)
This study had the objective of to describe the biology and management of the Tilletia barclayana, determine the effects of different rates of nitrogen topdressing application on the incidence and severity of kernel smut on irrigated rice, to assess the level of crop damage, and to determine the effectiveness of fungicide applied in different rice stages. To achieve these objectives, it was conducted two field experiments at Dona Francisca City, Rio Grande do Sul state, in the 2007/08 growing season, using the IRGA 422 CL cultivar. The Experiment 1, using rates of 108 kg ha-1 and Experiment 2, 135 kg ha-1 N, being applied in both experiments four rates of Miclobutanil (75,150, 225 e 300 g ha-¹ de a.i.) and one rate of Trifloxistrobina e Propiconazole (93,75+93,75 g ha-¹ de a.i.). The results showed that there was no significant difference between the two N rates for grain yield, milling yield, whole grains and mass of thousand grains. The kernel smut incidence, number of infected grains and sterility of spikelets had the higher average under application of 135 kg ha-1 N. On the other hand, the amount of healthy grain and yield of broken grain had higher values with the application of 108 kg ha-1 N. The fungicide application in R3 proved to be more efficient when compared to the R4 application in both experiments. In regards to the active ingredients, it was observed in Experiment 1, higher efficiency of Trifloxystrobin and Propiconazole 93, 75 + 93, 75 g ha-¹ a.i. for the variable incidence and grain yield. In Experiment 2 was a higher average of variable healthy grain, lower average of sterility of spikelets under application of Myclobutanil 75 g ha-¹ a.i. For the average yield whole grain yield and mass of thousand grains had better result with application of Myclobutanil 300 g ha-¹ a.i.